Guided inquiry model assisted HOTS-Based worksheet for critical thinking ability in online learning during pandemic covid-19 - Dina Maulina; Via Aini; Berti Yolida; Rini Rita T Marpaung (JURNAL BIOEDUKATIKA, 2022)
The 21st century education requires students to have critical thinking skills. This research aim was to analyze the influence of the guided inquiry learning model assisted by student worksheets based on Higher Order Thinking Skills (HOTS) on students' critical thinking skills during online learning at Senior High School 1 Gadingrejo class XI Science Major. This research uses a quasi-experimental design with a pretest-posttest non-equivalent control group design. The samples in this study were students of Natural Science Major class, XI Science Major 2 as the control class, and XI Science Major 7 as the experimental class which was selected through purposive sampling technique. The research data consist of quantitative and qualitative. Quantitative data in the form of the average score of pretest, posttest, and N-Gain as a result of critical thinking skills were analyzed by independent sample t-test (Î±=0.05) using SPSS 25.0 For Windows. The results showed that there was a significant effect of application of the HOTS-based guided inquiry learning model on students' critical thinking skills during online learning (Sig. 0.010 < 0.05). The experimental class N-gain value of 0.65 is classified as medium category. Qualitative data in the form of a questionnaire on the implementation of online learning with an average percentage result of 64.2% which is included in the strong category. A total of 92% of students agree that the difficult questions in the HOTS-based worksheets help improve critical thinking skills. Therefore, the guided inquiry learning model assisted by HOTS-based worksheet student has an effect on students' critical thinking skills during online learning.